Adam Józef Potocki (1822-1872) - Sendor, Albert Konrad (Wydawnictwo Księgarnia Akademicka, 2021)
The dissertation describes the life and activities of the Polish aristocrat Adam Józef Potocki (1822-1872). The research were based here on manuscripts and printed sources, literature, and iconographic materials. The objective of this work is to present a new approach to the figure of this politician from Galicia, and a critical evaluation of his activities, with special consideration given to the scope of his acts and all the initiatives he undertook. The main value of the dissertation is determined by improved knowledge about Adam Potocki’s life and activities, which has provided a new perspective of known historical events through measures taken by this politician. The dissertation can also act as a guideline for researchers dealing with the history of the 19th century. The focus here is to present Adam Józef Potocki against the background of the major events of the 19th century: the transformation of the Habsburg monarchy, and the impact of Polish politicians on such changes. The research has also attempted to capture transformations in the attitude of Adam Potocki, his involvement in state matters, and response to crisis situations. The politician’s characteristics made on the basis of available sources serves to show Potocki’s important role in the nineteenth-century Galicia. The research method applied in the work involved the synthetic and analytic analysis of sources. The query was performed in 20 archives and libraries, both in Poland and abroad, and included: 165 archival sources, 222 printed sources, 3 academic dissertations, 247 elaborations, 5 web documents.